CHARACTERISTICS OF THE US AND NATO STRATEGY TOWARDS THE FRY BEFORE AND DURING THE 1999 AGGRESSION - Miljković, Milan Đ; Jevtić, Dragan (Political Review, 2025)
In 1999, from the perspective of geopolitical developments in Europe, the Federal Republic of Yugoslavia was in a situation of the strategic expansion of NATO towards the central part of the continent. At the same time, the process of strengthening the position of this Alliance in the Balkans was underway. The paper analyzes the applied strategies of the USA and NATO in the period preceding the NATO aggression against the FRY, as well as during the aggression in 1999, using the theoretical model of the "continuum of strategies" with the aim of identifying the type, goals, and methods of their implementation. From the strategies of "soft" coercion through economic, political, and legal means, until the beginning of the aggression, "physical" coercion was implemented through the use of terrorism by the KLA in Kosovo and Metohija, which continued during the aggression. As often in the history of warfare, the beginning of the aggression against the FRY had the characteristics of an annihilation strategy, the elements of which are recognized in the military goals of the USA and NATO to degrade the military capabilities of the Yugoslav Army in a rapid military action and thus force the military and political leadership of the FRY to surrender. However, given that NATO’s plans were not implemented on the ground, and that the Yugoslav Army offered solid resistance, the complete military aggression against the FRY began to take on the characteristics of a strategy of destruction in practice after the first month of the war, as the dominant strategy throughout the conflict, given the intensification of fighting against military and especially civilian targets. The bombing of civilian targets in the FRY caused enormous material damage, estimated at around 100 billion dollars (Đorđević 2002, 231–245). Hospitals, health centers, schools, media institutions, road and railway infrastructure, substations, water supply systems, and other infrastructure were destroyed. The prerequisite for the implementation of this strategy was provided by NATO, which had enormous advantages in military capabilities compared to the Yugoslav Army. Also, NATO aggression against the FRY under the guise of "humanitarian intervention" had, in addition to the forcible installation of its forces in Kosovo and Metohija, one of the main goals of the regime change in Serbia, which implies the application of subversion and decapitation strategies in the form of colored revolutions or the installation of political leaders of the attacked states. The strategy of decapitation, which was launched more intensively in early 1999, was implemented over a longer period of time, both with the NATO action of April 22, and with the constant application of measures to strengthen the internal dissatisfaction of citizens with the regime of Slobodan Milošević. These strategies were partially implemented in October 2000 with the change of the regime. The features of the subversion strategy are not only visible in the events of October 2000 but it was also applied to international public opinion by staging the alleged "massacre" in the village of Racak on January 8, 1999. One of the most important features of the US and NATO strategies is that Slobodan Milošević was the central target throughout the entire duration of the aggression, against whom the strategy of coercion, subversion and decapitation were implemented, bearing in mind that the political leadership is at the center of the implementation of multiple strategies, according to the „5 rings" model. This is also evidenced by our famous historians, who point out that “diplomacy and psychological pressure on Milošević in the negotiations achieved more than NATO actions on the ground”. This leads to the conclusion that different strategies can be implemented simultaneously towards one important strategic goal for the enemy. It is also important to note that certain events during the preparation for the aggression, as well as during the aggression, contributed to the implementation of multiple strategies, such as the Rambouillet negotiations. Also, if the NATO action of April 22, 1999, resulted in the liquidation of the President of the Federal Republic of Yugoslavia, this event would mean not only that the decapitation strategy was implemented, but that its implementation would have effects that contribute to the strategy of dislocation of the enemy, and thus achieve cumulative effects against the enemy. A comparative analysis of the relevant literature indicates that the strategies implemented by the USA and NATO before and during the aggression on the FRY in 1999, as well as a year later during the change of the regime of Slobodan Milošević in October 2000, fit, according to their characteristics, into the spectrum of strategies that theorists Bowdish and Echeverria define as a "continuum of strategies". In conclusion, it can be stated that in the period taken for analysis, from 1998 to 2000, the USA and NATO used almost the entire range of offensive military strategies against the FRY.